Remediation of cyanide-contaminated environments through microbes and plants: a review of current knowledge and future perspectives. Issue 1 (2nd January 2017) - Kumar, Rahul; Saha, Shouvik; Dhaka, Sarita; Kurade, Mayur B.; Kang, Chan Ung; Baek, Seung Han; Jeon, Byong-Hun
Abstract: Mining industry has been using cyanide for more than ten decades to recover precious metals such as gold and silver. The presence of cyanide in the environment has long been a matter of concern due to its high toxicity to human, animal, and aquatic life. The available treatment processes either physical or chemical are suffered with issues such as operating conditions, generation of secondary pollution, and lack of cost effectiveness. A number of micro-organisms are capable to consume cyanide as a source of carbon and nitrogen, and convert it into ammonia and carbonate. Some plants are also efficient in cyanide attenuation process. Bioremediation of cyanide might be an efficient, cost-effective, eco-friendly, and an attractive alternative to the conventional physical and chemical processes. This paper reviews the recent advances in remediation of cyanide contaminated tailings via micro-organisms and plants. Aspects such as speciation, toxicity, source, and degradation mechanisms of cyanide are discussed. Factors affecting functioning of micro-organisms and plants as bioremediation agents are also highlighted.